+0  
 
0
59
1
avatar

Question:

Let f, g, and h be polynomials such that:
\(h(x) = f(x)\cdot g(x)\)
If the constant term of f(x) is -4 and the constant term of h(x) is 3, what is g(0)?

an help appreciated!

 Jul 26, 2020
 #1
avatar+110758 
+2

why not simplify the problem and let the 2 polynomials both be linear

m,n are both non zero and real.

 

\(f(x) = mx-4\\ g(x)= nx+k\\ \\~\\ h(x)= (mx-4)(nx+k) = ( some\; number)x^2 + ( some \;number )x   -4k\\ but\\ -4k=3\\ so\\ k=-\frac{3}{4}\)

 

 

So      g(0) = -3/4

 Jul 26, 2020

26 Online Users

avatar
avatar
avatar